The role of procurement specifications in curbing wrong deliveries of construction materials in the construction sector in Zimbabwe. Issue 1 (1st January 2019) - Munyimi, Tinotenda Fredrick
Abstract: This research is on the role of procurement specifications in curbing wrong deliveries of construction materials in the construction sector. The researcher has reviewed both practitioners and academic literature. This research method was a cross-industry survey of construction companies. The population of this research was made up of the staff members of the procurement management departments of the companies in the construction sector. This research used purposive sampling to select construction companies. A sample of 56 procurement practitioners out of the total population of 65 procurement employees in the construction sector was selected randomly. Primary data were collected in a comprehensive survey close-ended questionnaire from procurement practitioners working in the construction sector and supported by an open-ended interview with procurement managers only. The researcher calculated descriptive and inferential statistics using the Statistical Package for Social Science software (Version 22), where quantitative findings were tabularized. The hypothesis was tested utilising the one-way analysis of variance (ANOVA) and multiple linear regression analysis. This research reveals that there is a positive significant correlation of the three types of procurement specifications in curbing wrong deliveries of construction materials, namely, performance specifications, brand or trade name specifications and sample specifications. The results of this research imply that practicing procurement directors, procurement managers, procurement officers, buyers and procurement assistants should use performance specifications for construction materials with specific purpose, function or application, brand or trade name specifications for construction materials that rely on brand names known for their proven quality and sample specifications on construction materials with complex specifications to curb wrong deliveries of construction materials in the construction sector. This research provides reliable baseline data for future research into would these procurement specifications help curtail construction projects risk and would they provide support should there be any legal disputes between the procurer and the supplier.